2018
DOI: 10.1093/cid/ciy827
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole Versus Caspofungin in the Treatment of Candidemia and Other Invasive Candida Infections: The ACTIVE Trial

Abstract: In a phase 3, randomized, double-blind, multinational clinical trial comparing isavuconazole to caspofungin for primary treatment of patients with proven candidemia or invasive candidiasis, isavuconazole failed to demonstrate noninferiority compared with caspofungin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 22 publications
6
86
1
7
Order By: Relevance
“…Reports have suggested that as many as one-third of all patients with disseminated Candida infections fail to respond to antifungal therapy (10,(36)(37)(38)(39). Both intrinsic and acquired mechanisms of antifungal drug resistance are known to reduce the chances of successful treatment of IFIs (11).…”
Section: Discussionmentioning
confidence: 99%
“…Reports have suggested that as many as one-third of all patients with disseminated Candida infections fail to respond to antifungal therapy (10,(36)(37)(38)(39). Both intrinsic and acquired mechanisms of antifungal drug resistance are known to reduce the chances of successful treatment of IFIs (11).…”
Section: Discussionmentioning
confidence: 99%
“…Even if Candida spp. Are sensitive to azoles, therapy with an echinocandin is recommended as it was shown to be superior in a septic ICU population with invasive candidiasis and candidaemia [53,54]. Several population pharmacokinetic studies in a general ICU population suggested that echinocandins are probably underdosed and no dose reduction is required for patients on CRRT [55,56].…”
Section: De-escalationmentioning
confidence: 99%
“…179 Echinocandins appear to be as effective as and better tolerated than amphotericin B formulations 180,181 and, in two randomized trials, more effective than azoles. 182,183 Particularly, in one of these trials including 245 patients with IC (89% of them with candidemia only) anidulafungin treatment resulted in superior combined clinical and microbiological response compared with fluconazole (at 2 weeks 65 vs. 49%), although no differences were observed at 60-day mortality rates. 182 The use of echinocandins is further supported by a quantitative review of RCTs (1,915 patients, seven studies) showing that treatment with echinocandins led to decreased mortality (OR: 0.65; 95% CI: 0.45-0.94) and increased treatment success (OR: 2.33; 95% CI: 1.27-4.35).…”
Section: Treatmentmentioning
confidence: 99%